w-conotoxina MVIIA isolada ou associada ao dantrolene sódico no trauma medular agudo em ratos - Karen Maciel de Oliveira (2014)
Three experiments were performed. Experiment 1 evaluated the neuroprotective potential of -conotoxin MVIIA (MVIIA) at different doses, via intralesional and intrathecal in rats after acute spinal cord injury with mitochondrial viability, cell death, glutamate levels, production of reactive oxygen and lipid peroxidation assays. Defining the proper dose and route, it was also evaluated the time of application, acute (60 minutes) and subacute (four hours), after spinal cord trauma. After setting the time of application, it was evaluated the gene expression of apoptosis-related factors. Experiment 2 assessed the antioxidants effects of MVIIA after acute spinal cord injury in rats, quantifying of superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx), glutathione-S-transferase (GT) and glutathione reductase (GR). Experiment 3 evaluated the antioxidant and neuroprotective effect of calcium channel blockers association, MVIIA and dantrolene, in rats after acute spinal cord injury. The experiment 1 showed that the MVIIA applied intrathecally, four hours after the trauma, at a dose of 10 M has neuroprotective effect reducing neuronal death in 22.46% ± 2.99, oxidative stress, expression of pro-apoptotic factor (Bax), caspase-3, caspase-8, nNOS and increased mitochondrial viability and anti-apoptotic factor (Bcl-xl). The experiment 2 suggested that a pathway of MVIIA neuroprotection was provided due to its antioxidant effects, with increase, related to placebo, in enzymes SOD (188.41% ± 72.05), GP (199.96% ± 68.65), GR (193.86% ± 59.39) e GT (175.93% ± 68.92). The experiment 3 showed that there was no cell death reduction in association of MVIIA and dantrolene (82.70% ± 17.02), despite declining ERO (68.34% ± 17.33) and increasing GR (229.18% ± 116.58). It was concluded that MVIIA has a neuroprotective potential and the possible mechanisms are related to modulation of antioxidant system and apoptosis pathways intrinsic and extrinsic. Moreover, there was not effect of pharmacological addition on the association MVIIA and dantrolene.